Conference at the Museum of Modern Art Norrkopinkg Sweden - (:unkn) unknown (My University, 2026)
Is this the Time for Art? How to Represent the Unrepresented Conference at the Museum of Modern Art Norrkopinkg Sweden. Collaboration between The Museum of Forgetting (www.museetforglomska.se), ACSIS (Advanced Cultural Studies Institute of Sweden), Linköping University and Norrköping Art Museum.” “Klitsa Antoniou: Loss, Trauma, Affect and how the Material Passes into a Sensation.”